DIRECT METHODS IN X-RAY CRYSTALLOGRAPHY (Web of Technology: Multidimensional Research Journal, 2025)
The paper considers the history of the creation of a direct method of X-ray structural analysis. There are 230 combinations of symmetry elements that a crystal structure, which are called space groups. The Bragg X-ray diffraction scheme, the structure of a sandwich complex of a mercury-containing macrocycle with borane, and the atomic scattering curves for a point atom, a stationary atom, and an atom undergoing thermal vibrations are studied.